Effect of Lead Addition in LM6 Alloy Castings - S.THIRU,, CHITRAMBALAM (The Institution of Indian Foundrymen, 2010)
In this research work, lead is added in the LM6 alloy melt and casting samples in the form of a slab are made by pouring the treated alloy in the sand moulds. Lead is added in the range from 2% to 14% in the chosen LM6 alloy. The chosen pouring temperature was around 800 degree centigrade. In this work, effect of lead on the hardness, microstructure and impact strength are discussed. Besides, corrosion resistance tests are conducted and the results are discussed. Fracture surface studies are also conducted on the samples after the impact test and fractographs are captured to analyse the type of failure.